In vitro functional evaluation of isolaureline, dicentrine and glaucine enantiomers at 5‐HT2 and α1 receptors. (3rd October 2018) - Heng, Hui Li; Chee, Chin Fei; Thy, Chun Keng; Tee, Jia Ti; Chin, Sek Peng; Herr, Deron R.; Buckle, Michael J. C.; Paterson, Ian C.; Doughty, Stephen W.; Abd. Rahman, Noorsaadah; Chung, Lip Yong
Abstract: Compounds with activity at serotonin (5‐hydroxytryptamine) 5‐HT2 and α1 adrenergic receptors have potential for the treatment of central nervous system disorders, drug addiction or overdose. Isolaureline, dicentrine and glaucine enantiomers were synthesized, and their in vitro functional activities at human 5‐HT2 and adrenergic α1 receptor subtypes were evaluated. The enantiomers of isolaureline and dicentrine acted as antagonists at 5‐HT2 and α1 receptors with ( R )‐isolaureline showing the greatest potency (p K b  = 8.14 at the 5‐HT2C receptor). Both ( R )‐ and ( S )‐glaucine also antagonized α1 receptors, but they behaved very differently to the other compounds at 5‐HT2 receptors: ( S )‐glaucine acted as a partial agonist at all three 5‐HT2 receptor subtypes, whereas ( R )‐glaucine appeared to act as a positive allosteric modulator at the 5‐HT2A receptor. Abstract : The ( R )‐ and ( S )‐enantiomers of isolaureline and dicentrine act as antagonists at 5‐HT2 and α1 receptors with ( R )‐isolaureline showing the greatest potency (p K b  = 8.14 at the 5‐HT2C receptor). Both ( R )‐ and ( S )‐glaucine also antagonize α1 receptors, but the two enantiomers behave very differently at 5‐HT2 receptors: ( S )‐glaucine acts as a partial agonist at all three 5‐HT2 receptor subtypes, whereas ( R )‐glaucine appears to act as a positive allosteric modulator at the 5‐HT2A receptor.